The complexity of the mind: rejecting modularity on the basis of cognitive penetration and cognitive phenomenology - Hershberger, Joelle, author; MacKenzie, Matthew, advisor; Tropman, Elizabeth, committee member; Rhodes, Matthew, committee member (Colorado State University. Libraries, 2018)
Historically, cognitive scientists and philosophers have accepted a theory of the mind known as modularity, whereby individual thought processes are completely separate and insulated from one another—meaning that cognitions have no influence on perceptions. However, the recent literature has seen a resurgence in support of a thesis of cognitive penetration, which suggests that cognitions can and do influence perceptions in a way that would be impossible if the mind were modular in the traditional sense. In addition to calling the idea of modularity into question, cognitive penetrability raises some passing concerns for the objectivity of scientific observation, and certain philosophical distinctions such as that between cognition and perception. Along similar lines, the literature has also seen an increase in the exploration of cognitive phenomenology, which similarly calls into question the distinction between cognition and perception and requires a model of the mind which is less clear-cut than the modular view. As such, it seems that given the evidence, one cannot accept either penetrability or cognitive phenomenology without accepting the other, given that they both rest on a similar view of the mind. In addition to calling into question the literal distinction between cognition and perception (though it may remain intact on a conceptual level), a subsection of cognitive phenomenology, known as evaluative phenomenology (the unique phenomenal character of emotions) similarly makes ambiguous the philosophical distinction between reason and emotion. Breaking this dichotomy, as well, makes the possible epistemic consequences of penetrability pale in comparison to those implied by cognitive phenomenology. While this is not an answer to the issues raised by penetrability, it does contextualize the difficulties in a way which opens the system up to a deeper understanding.
Keywords: Fodor; penetration; cognition; phenomenology; modularity